Lines Traversing Space: Mediation Proposals for Public Art Using 3D Pens - Kumm, Rosely (Revista do Colóquio, 2026)
This article stems from research conducted at the Art Extension and Research Laboratory (LEENA-UFES), focusing on mediation proposals to promote the appreciation of public art in Espírito Santo. The study investigates the use of the 3D pen as a mediation tool in art education, using monuments from Espírito Santo as a reference. This research is presented here through two workshops: one with students from the municipal Youth and Adult Education program, and another with people with disabilities attending an APAE center. The proposal integrates visual, tactile, and cognitive dimensions, fostering connections between the artworks, their socio-historical contexts, and the audience’s experience. Thus, the aim is to incorporate emerging technologies into the field of art education as a strategy to enhance the enjoyment, understanding, and appreciation of cultural heritage.